2006
DOI: 10.1007/s00198-006-0084-3
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D insufficiency and the blunted PTH response in established osteoporosis: the role of magnesium deficiency

Abstract: This study confirms that in patients with established osteoporosis, there is also a distinct group with a low vitamin D and a blunted PTH level and that Mg deficiency (as measured by the Mg loading test) is an important contributing factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(35 citation statements)
references
References 29 publications
2
29
0
1
Order By: Relevance
“…This phenomenon has been repeatedly reported, and some studies suggested other factors that could have a role. Sahota et al called it ''blunted PTH'' [10] and tested the hypothesis that magnesium deficiency could be partly responsible by giving a magnesium load to individuals with HD without SHP [14]. Mean serum PTH levels increased 13.3 ng/l in their subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon has been repeatedly reported, and some studies suggested other factors that could have a role. Sahota et al called it ''blunted PTH'' [10] and tested the hypothesis that magnesium deficiency could be partly responsible by giving a magnesium load to individuals with HD without SHP [14]. Mean serum PTH levels increased 13.3 ng/l in their subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, high calcium ingestion [13], low serum albumin levels [9], and magnesium deficiency [14] were also associated with a smaller PTH response to HD. Recently, SHP in HD individuals was associated with a higher mortality when compared to individuals with HD and without SHP [15].…”
mentioning
confidence: 98%
“…It is not clear whether this lower response of serum PTH to lower serum 25(OH)D levels in African-American men represents a difference between study populations, or due to other factors such as magnesium deficiency [29][30][31][32][33]. Subclinical magnesium insufficiency prevents an adequate response of PTH to low 25(OH)D and PTH rises appropriately after magnesium supplementation [30]. We did not evaluate magnesium insufficiency in our population but magnesium insufficiency is commonly seen in chronic conditions that are prevalent in our population.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 Magnesium shortage is clinically associated with osteoporosis, vitamin D deficiency and a blunted PTH response. 36,37 Magnesium deficiency may occur in any bypass reconstruction, because it binds with fatty acids out of dietary fat and with products of bacterial fermentation. In other words, optimization of calcium metabolism is only possible if dietary magnesium and resorption are appropriate.…”
Section: Calcium/magnesium Sensing Receptor (Casr) For Passive Calciumentioning
confidence: 99%